Extraction of fucoxanthin from Chaetoceros calcitrans by electropermeabilization-assisted liquid biphasic flotation system - Khoo K.S.; Ooi C.W.; Chew K.W.; Chia S.R.; Foo S.C.; Ng H.S.; Show P.L. (Elsevier B.V., 2023)
Antioxidants; Flotation; Liquids; Molecular biology; Bio-compounds; Bioprocessing; Bubble separation; Chaetoceros calcitrans; Electropermeabilization; Electropermeabilization-assisted; Electroporation; Extraction systems; Fucoxanthin; Liquid biphasic flotation; Extraction; alcohol; copper; fucoxanthin; sodium chloride; fucoxanthin; xanthophyll; antioxidant activity; Article; biomass; bioprocess; Chaetoceros; Chaetoceros calcitrans; concentration (parameter); controlled study; diatom; electric potential; electroporation; extraction; flotation; flow rate; liquid biphasic flotation; nonhuman; partition coefficient; diatom; electroporation; microalga; Diatoms; Electroporation; Microalgae; Xanthophylls